The Emergency of Being On Heidegger’s "Contributions to Philosophy" - Polt, Richard (Cornell University Press, 2013)
"The heart of history, for Heidegger, is not a sequence of occurrences but the eruption of significance at critical junctures that bring us into our own by making all being, including our being, into an urgent issue. In emergency, being emerges."—from The Emergency of BeingThe esoteric Contributions to Philosophy, often considered Martin Heidegger's second main work after Being and Time, is crucial to any interpretation of his thought. Here Heidegger proposes that being takes place as "appropriation." Richard Polt's independent-minded account of the Contributions interprets appropriation as an event of emergency that demands to be thought in a "future-subjunctive" mode. Polt explores the roots of appropriation in Heidegger's earlier philosophy; Heidegger's search for a way of thinking suited to appropriation; and the implications of appropriation for time, space, human existence, and beings as a whole. In his concluding chapter, Polt reflects critically on the difficulties of the radically antirationalist and antimodern thought of the Contributions.Polt's original reading neither reduces this challenging text to familiar concepts nor refutes it, but engages it in a confrontation—an encounter that respects a way of thinking by struggling with it. He describes this most private work of Heidegger's philosophy as "a dissonant symphony that imperfectly weaves together its moments into a vast fugue, under the leitmotif of appropriation. This fugue is seeded with possibilities that are waiting for us, its listeners, to develop them. Some are dead ends—viruses that can lead only to a monolithic, monotonous misunderstanding of history. Others are embryonic insights that promise to deepen our thought, and perhaps our lives, if we find the right way to make them our own."